Bariery rozwoju i ich ujęcie w planowaniu terytorialnym - Wojtasiewicz, Lucyna (Wydział Prawa i Administracji UAM, 1979)
A development process encouters limits of different kinds. To left the development follow harmoniously one should recognize these obstacles right early and neutralize them. Also the development must be shaped in such manner to cause emergence of new limits in possibly small extent. Research on limits to the growth should be based on regard to spatial interdependence of particular growth elements. It is essential in understanding the problem that spatial relations existing between particular development factors — if unsuitable — can constitute a limit to the growth. Balance calculations considering internal and external sectors of particular regions and mutual interaction of these sectors should be then a tool for identification and measurement of limits to the growth.
Limits to the Development and Their Understanding in Territorial Planning